Characterizing regional aerosol pollution in central China based on 19 years of MODIS data: Spatiotemporal variation and aerosol type discrimination. (August 2020) - Shen, Lijuan; Wang, Honglei; Zhao, Tianliang; Liu, Jane; Bai, Yongqing; Kong, Shaofei; Shu, Zhuozhi
Abstract: Recently, the frequent occurrence of haze with aerosol pollution in China has attracted worldwide attention. Air pollutant emissions in conjunction with changing meteorological conditions create environment pollution in China. Aerosol pollution is spatially centralized in four regions of China, including the North China Plain, Yangtze River Delta, Pearl River Delta, and Sichuan Basin. In this observational study, a new center of aerosol pollution was identified in the Twain-Hu Basin (THB), covering the Hubei and Hunan provinces in central China. Based on the analysis of 19 years of satellite remote sensing data from the Moderate Resolution Imaging Spectroradiometer (MODIS), the THB experiences high aerosol optical depth (AOD) values exceeding 0.9. The fine mode fraction (FMF) values below 0.3 were also detected over the aerosol polluted THB region, where aerosol pollution was dominated by the mixed aerosol type. This reflects the role of intense human activities and the unique aerosol processes involved in the regional aerosol pollution over central China. The interannual AOD variations for THB present an increasing trend (mostly >0.02 yr −1 ) between 2000 and 2011 and a significant descending trend (mostly < -0.06 yr −1 ) between 2011 and 2018. This inverse trends in AOD with an overall increasing trend in FMF characterizes the past 19 years. This highlights the contribution of the increase in submicron particles and meteorological effects to the regional aerosol concentrations during recent years when considering the reduced anthropogenic aerosol emissions in the THB. Graphical abstract: Image 1 Highlights: An area of high aerosol concentrations was identified over central China. The trends in AOD changes were contrary between 2000-2011 and 2011–2018. Submicron aerosols increased in the sub-basin of central China over 2000–2018. Seasonal heterogeneity in aerosol type impacted environment of central China.